Respuesta :

Answer:

The point-slope formula states:

(

y

y

1

)

=

m

(

x

x

1

)

Where

m

is the slope and

(

x

1

y

1

)

is a point the line passes through.

Substituting the slope and one of the points gives:

(

y

6

)

=

14

(

x

4

)

(

y

+

6

)

=

14

(

x

+

4

)

We can now solve for

y

to put the equation in the slope-intercept form.

y

+

6

=

14

x

+

(

14

×

4

)

y

+

6

=

14

x

56

y

+

6

6

=

14

x

56

6

y

+

0

=

14

x

62

y

=

14

x

62

Step-by-step explanation:

Work on this answer

ACCESS MORE